2018
DOI: 10.1021/acsnano.8b01532
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered Wind Sensor System for Detecting Wind Speed and Direction Based on a Triboelectric Nanogenerator

Abstract: The development of the Internet of Things has brought new challenges to the corresponding distributed sensor systems. Self-powered sensors that can perceive and respond to environmental stimuli without an external power supply are highly desirable. In this paper, a self-powered wind sensor system based on an anemometer triboelectric nanogenerator (a-TENG, free-standing mode) and a wind vane triboelectric nanogenerator (v-TENG, single-electrode mode) is proposed for simultaneously detecting wind speed and direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
142
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 260 publications
(143 citation statements)
references
References 44 publications
1
142
0
Order By: Relevance
“…In cases like continuous monitoring, off-the-grid, and maintenance-free applications, self-powered sensors would be extremely desirable.Toward this aim, several energy harvesting strategies have been explored, based on triboelectricity, [4] piezoelectricity, [5] pyroelectricity, [6] and others. Examples of such devices include health monitoring devices, [1] soft robotics, [2] and functional artificial skin.…”
mentioning
confidence: 99%
“…In cases like continuous monitoring, off-the-grid, and maintenance-free applications, self-powered sensors would be extremely desirable.Toward this aim, several energy harvesting strategies have been explored, based on triboelectricity, [4] piezoelectricity, [5] pyroelectricity, [6] and others. Examples of such devices include health monitoring devices, [1] soft robotics, [2] and functional artificial skin.…”
mentioning
confidence: 99%
“…These TENG-based sensors have been considered as one of the most effective mechanical energy conversion technologies as they enable the generation of high open-circuit voltage at a low frequency. Based on an anemometer TENG and a wind vane TENG, J. Y. Wang et al [16] presented a wind sensor with a sensing range from 2.7 to 8.0 m s −1 , which generates an output short-circuit current of 6.3 µA at wind speed of 6 m s −1 . [14] Y. Yang et al [15] reported a TENG-based wind speed sensing system, which displays a sensitivity of 0.09 µA/(m/s) and a detection limit 6 m s −1 by utilizing the wind-induced vibration.…”
Section: Introductionmentioning
confidence: 99%
“…The high sensitivity of TENG toward tiny vibration, the cost-effective fabrication process, and the flexible device structure provide much possibilities for the smart and interesting applications, such as humidity sensor, [10] pressure sensor, [11] active acoustic sensor, [12] ultraviolet detector, [13] Keystroke dynamics identification, [14] handheld printer, [15] and so on.Machine learning (ML) [16,17] is usually referred to statistical models and algorithms used by computer systems to conduct a specific task without too much complex instructions. The high sensitivity of TENG toward tiny vibration, the cost-effective fabrication process, and the flexible device structure provide much possibilities for the smart and interesting applications, such as humidity sensor, [10] pressure sensor, [11] active acoustic sensor, [12] ultraviolet detector, [13] Keystroke dynamics identification, [14] handheld printer, [15] and so on.…”
mentioning
confidence: 99%